2014
DOI: 10.1186/s40510-014-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Torque expression capacity of 0.018 and 0.022 bracket slots by changing archwire material and cross section

Abstract: Background: The aim of this study is to calculate and compare the play and torque expression of 0.018 and 0.022 bracket slots when engaged with archwires of different size, cross section and material. Methods: Eight orthodontic brackets, two of slot height 0.018 and six of slot height 0.022, from different manufacturers, were measured and fixed to a vertical support. Twenty-four archwires of differing size, cross section and material were selected, measured and tested in each bracket of compatible slot width. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 18 publications
7
57
2
4
Order By: Relevance
“…Reversing the formula, considering the slot height as a constant (0.0220 for rectangular archwires and 0.0180 for square archwires) and inserting the real bevel radius, the resulting calculation yields the play. As expected from the literature, 4 this calculation revealed that in the real world the play is invariably greater than the ideal, within the range +34% to +313%. Translated into degrees, the increase in play seen in our sample ranged from +1u (Ormco 0.021 3 0.0250 NiTi heat activated) to +17u (Ormco 0.017 3 0.0220 SS) with respect to the ideal.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Reversing the formula, considering the slot height as a constant (0.0220 for rectangular archwires and 0.0180 for square archwires) and inserting the real bevel radius, the resulting calculation yields the play. As expected from the literature, 4 this calculation revealed that in the real world the play is invariably greater than the ideal, within the range +34% to +313%. Translated into degrees, the increase in play seen in our sample ranged from +1u (Ormco 0.021 3 0.0250 NiTi heat activated) to +17u (Ormco 0.017 3 0.0220 SS) with respect to the ideal.…”
Section: Discussionsupporting
confidence: 60%
“…3,4,[7][8][9] This is confirmed by our measurements, although we found that the stated measurements were more precise than those reported by other authors, with a tolerance range of 26.47% to +5.10%, as opposed to the 17% reported elsewhere. 6 The role of the archwire edge bevel has not yet been studied in depth.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…However, Confidence brackets exhibited significant differences in the manufacturing errors of torque. [19] Another study showed that even with the use of a similar wire, the brackets of different companies exhibited different play and torque functions, and in all the brackets evaluated, the dimensions of the slot were larger than those reported by the manufacturers,[22] which was similar to the results reported by Cash et al . [15]…”
Section: Discussionsupporting
confidence: 74%